Cardiovascular Disease and COVID-19: What’s the Issue? - Putra, Bayushi Eka; Santoso, Anwar (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
What’s our status? As per 17 April 2020, Indonesia has the most confirmed cases (5.923 cases) of Coronavirus Disease (COVID-19) among Southeast Asian Countries.1 Considering the daily increase of cases, we are considered nowhere near the plateau of the epidemic curve. It was predicted that the peak may be reached from May to June.2 Predictably, this will not end soon. COVID-19 contracted patients may also vary in severity. The patient may present with no symptoms, mild to moderate, and severe condition. Mild (81%) depicted as COVID-19 patients with no evidence or mild pneumonia, severe (14%) for COVID-19 patients with hypoxia and greater than 50% lung involvement within 24-48 hours, critical (5%) if the patient develops shock, acute respiratory distress syndrome, myocarditis, or even organ failure which need intensive care, and 2.3 % were fatal which end up in death.3,4